Using marine protected areas to assess the status and recovery of the spiny lobster Jasus edwardsii fishery in the Hauraki Gulf, Aotearoa New Zealand - Nessia, Hayley R.; Hanns, Benn J.; Haggitt, Tim R.; Shears, Nick T. (Frontiers in Marine Science, 2024)
The value of no-take marine protected areas (MPAs) in providing fisheries-independent information to evaluate the status of adjacent fish stocks is increasingly being recognised. However, to ensure robust assessments of fisheries using this approach, MPAs need to be representative of the wider fished area and sampling should include multiple MPA and fished locations spanning the area of interest. The spiny lobster Jasus edwardsii fishery in Aotearoa New Zealand’s Hauraki Gulf has been in decline since the late 1990s, but latest stock estimates suggest a dramatic recovery following catch reductions in 2018. We compared J. edwardsii populations on shallow reefs (<20 m depth) in three marine reserves with six fished locations across the Hauraki Gulf to provide a fisheries-independent assessment of this important fishery and the degree of recovery following catch reductions. Region-wide surveys found that J. edwardsii populations within protected areas were dominated by large, legal-size individuals, whereas lobster in fished locations were mostly below or around legal-size. Total, vulnerable, and spawning stock biomass was 12-43 times higher within MPAs compared to fished locations. Overall, biomass at fished locations was <10% of that in reserves and there was little evidence of recovery following catch reductions. Our fisheries-independent data suggest that recent stock assessments have severely overestimated the recovery and state of lobster populations in the Hauraki Gulf and that populations on shallow reefs remain depleted. These findings highlight the critical need for fisheries-independent data and the value of MPA monitoring data in evaluating population status and recovery following fisheries management actions.